ASSOCIATION OF MODELING MASSAGE WITH MANUAL LYMPHATIC DRAINING IN AESTHETICS (Fiep Bulletin - online, 2019)
The beauty market is the segment that grows exponentially all over the world. The search for the perfect body andyouthful appearance drives investments, innovation research, technology advancement and professional training. Being acomprehensive segment is also great the volume of advertisements and marketings around the procedures. Lymphatic drainageand modeling massage are already well-established techniques in treatments, quite effective and popular. In recent years theyhave achieved greater prominence, since they have been inserted in "certified methods" and a "drainage" massage with verystrong marketing calls for weight loss. In the scientific field there is still a shortage of works with reliable methodologies, whichfavors the creation of these protocols in a booth, and posthumously disseminated among professionals. Objective: to investigatethe physiological effects and the association between massage and drainage in a single treatment session. Methodology: abibliographical review was carried out through a reading and database specific to the health area, of scientific articles such asPubMed, Scielo, Google Academic and Periodicals from 2004 to 2018. Results: 28 studies were found, 13 of which were selectedthe inclusion criteria: 7 are clinical trials in humans that tested the effectiveness, 1 comparative clinical study of the techniques, 2are case studies, 3 bibliographic reviews on the techniques and their concepts. Conclusion: The decrease in body weight andperimetry is due to the increase in diuresis caused by fluid mobilization and improvement of lymphatic stasis, controversiesregarding the effects of modeling massage and associated lymphatic drainage are suggested. test efficacy and furtherclarification.